ANALISIS SEBARAN INDEKS AKSESIBILITAS PENGINAPAN TERHADAP OBJEK WISATA DI KAWASAN MANDEH - fihansnur, henisya; Syarief, Azhari (JURNAL BUANA, 2024)
To increase tourism which can affect the social and economy, it is necessary to analyze the index of accommodation accessibility to tourist objects in the Mandeh Area, Koto XI District, Tarusan, Pesisir Selatan Regency. The research method used is descriptive analysis method using the accessibility index formula. Based on the research results, the accessibility index of lodging facilities to tourism objects has a very low accessibility index, low accessibility indeks, moderate accessibility index, high accessibility indeks, and very high accessibility index. Tourists can choose lodging facilities that can be reached by the tourist object they are going to.